The effect of localised stiffening on the stability of a flexible panel in uniform flow - Tan, B.; Lucey, A.; Howell, Richard (2014)
The three-dimensional stability of a fluid-loaded flexible panel is studied to determine the effectiveness of adding localised stiffening to control or postpone instability. A hybrid of computational and theoretical modelling is used to cast an eigenvalue problem for the fluid-structure system. It is shown that the addition of each of transverse and streamwise stiffening strips postpones divergence onset but for the former there is a threshold strip stiffness above which no further postponement is possible. Streamwise stiffening is additionally shown to be effective for increasing post-divergence flutter-onset flow speeds while in aero-elastic applications a transverse stiffening strip can be used to replace flutter instability with divergence. The present results suggest a relatively economical and practicable way to ameliorate panel instability in both hydro- and aero-elastic applications.